Epigenetic loss of heparan sulfate 3‐O‐sulfation sensitizes ovarian carcinoma to oncogenic signals and predicts prognosis. Issue 8 (9th August 2018) - Huang, Rui‐Lan; Chen, Hsiang‐Ju; Chen, Lin‐Yu; Chao, Tai‐Kuang; Lin, Wei‐Yu; Liew, Phui‐Ly; Su, Po‐Hsuan; Weng, Yu‐Chun; Wang, Yu‐Chi; Liao, Chi‐Chun; Hsu, Yaw‐Wen; Wang, Hui‐Chen; et al.
Abstract : Precision medicine requires markers for therapeutic guidance. The purpose of this study was to determine whether epithelial ovarian cancer (EOC) epigenetics can lead to the identification of biomarkers for precision medicine. Through integrative methylomics, we discovered and validated the epigenetic signature of NEFH and HS3ST2 as an independent prognostic factor for type II EOC in our dataset ( n  = 84), and two independent methylomics datasets (total n  = 467). Integrated transcriptomics dataset ( n  = 1147) and tissue microarrays ( n  = 54) of HS3ST2 also related to high‐methylation statuses and the EOC prognosis. Mechanistic explorations of HS3ST2 have assessed responses to oncogenic stimulations such as IL‐6, EGF, and FGF2 in cancer cells. The combination of HS3ST2 and various oncogenic ligands also confers the worse outcome. 3‐O‐sulfation of heparan sulfate by HS3ST2 makes ovarian cancer cells intrinsically sensitive to oncogenic signals, which sheds new light on the application of HS3ST2 as a companion diagnostic for targeted therapy using kinase inhibitors or therapeutic antibodies. Abstract : What's new? Most targeted therapies for epithelial ovarian cancer are ineffective. For precision medicine to be effective, companion diagnostic tests are needed. Through integrative epigenomics, here the authors discovered and validated the epigenetic signature of NEFH/HS3ST2 as a stratifying prognostic factor. Mechanistic investigations of HS3ST2 revealed inhibitory effects on various oncogenic signals and malignant phenotypes. Low HS3ST2 and overexpression of oncogenic ligands synergized to confer a poor outcome. Furthermore, 3‐O‐sulfation of heparan sulfate by HS3ST2 made ovarian cancer cells intrinsically sensitive to oncogenic signals, suggesting the application of HS3ST2 as a companion diagnostic for targeted therapy using kinase inhibitors or therapeutic antibodies.